2000
DOI: 10.3758/bf03209339
|View full text |Cite
|
Sign up to set email alerts
|

Associative recognition: A case of recall-to-reject processing

Abstract: Two-process accounts of recognition memory assume that memory judgments are based on both a rapidly available familiarity-based process and a slower, more accurate, recall-based mechanism. Past experiments on the time course of item recognition have not supported the recall-to-reject account of the second process, in which the retrieval of an old item is used to reject a similar foil (Rotello & Heit, 1999).In three new experiments, using analyses similar to those of Rotello and Heit, we found robust evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
187
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(208 citation statements)
references
References 56 publications
15
187
1
Order By: Relevance
“…For them to be combined this way means that item and associative retrieval processes must yield similar outputs. This is inconsistent with theories that posit qualitatively different mechanisms for item and associative retrieval, including most dual-process theories which assume either that item and associative retrieval are independent (via separate "familiarity" and "recollection" processes Yonelinas, 1997) or that associative retrieval can only serve to suppress an item match (via "recall-toreject"; Rotello & Heit, 2000) rather than enhance it. At the same time, the ability for mismatch information to arise separately from item and associative retrieval is not easily accommodated by either single-process or summed dual-process models (Kelley & Wixted, 2001) which entail pooling of both match and mismatch information into a univariate "memory strength".…”
Section: What Is Associative Retrieval?mentioning
confidence: 87%
See 3 more Smart Citations
“…For them to be combined this way means that item and associative retrieval processes must yield similar outputs. This is inconsistent with theories that posit qualitatively different mechanisms for item and associative retrieval, including most dual-process theories which assume either that item and associative retrieval are independent (via separate "familiarity" and "recollection" processes Yonelinas, 1997) or that associative retrieval can only serve to suppress an item match (via "recall-toreject"; Rotello & Heit, 2000) rather than enhance it. At the same time, the ability for mismatch information to arise separately from item and associative retrieval is not easily accommodated by either single-process or summed dual-process models (Kelley & Wixted, 2001) which entail pooling of both match and mismatch information into a univariate "memory strength".…”
Section: What Is Associative Retrieval?mentioning
confidence: 87%
“…We address one final point demonstrated in prior studies of retrieval dynamics, namely, that associative retrieval is slower than item retrieval (Gronlund & Ratcliff, 1989;Rotello & Heit, 2000). From the viewpoint that associative information arises from the unitization of item information, it is clear that associative retrieval depends on having sufficient item information for a unit to be formed "on the fly" within the trial.…”
Section: What Is Associative Retrieval?mentioning
confidence: 90%
See 2 more Smart Citations
“…Instead, they found that, although participants could reject novel foils (XY) more quickly when given a 200 ms head start, that same time conferred no advantage in rejecting AB' foils. Rotello and Heit (2000) contend that 200 ms is quite brief and may not have been long enough to allow for participants to use the first word as a retrieval cue, since it would take participants roughly that amount of time to even read the word. Nobel and Shiffrin (2001) directly compare the dynamics of cued recall and associative recognition in a set of signal-to-respond experiments (in recall, participants either generated a response word immediately after the signal or were allowed to make a "give up" response).…”
Section: Associative Recognitionmentioning
confidence: 99%